PELATIHAN PENGELOLAAN USAHA DENGAN TEKNIK PEMASARAN MARKETPLACE DI DESA JAMBUGEULIS KECAMATAN CIGANDAMEKAR KABUPATEN KUNINGAN - Tito Sugiharto; heri Herwanto; Rio Andriyat Krisdiawan; erik Kurniadi (Indonesian Community Service and Empowerment Journal (IComSE), 2022)
Jambugeulis Village is one of the villages in Kuningan Regency whose people generally have a livelihood as farmers and day laborers. Apart from being farmers and daily laborers, the people of Jambugeulis village also have jobs as traders and home-made food makers. There are several types of home-cooked food produced by the people of Jambugeulis village, including moring (a type of small cracker made from tapioca flour), cassava tape food, and cuhcur cake. The people of Jambugeulis village in the process of marketing traditional food products still use conventional methods, namely by selling products directly to consumers and in collaboration with traditional food gift shops. The conventional sales process has several shortcomings/weaknesses including the marketing process of traditional food products is still limited only in Kuningan Regency, the profit of the Jambugeulis village community is slightly reduced from the normal selling price due to a reduction in distribution costs. The difficulty of access for consumers from outside the Kuningan Regency to buy/obtain traditional food products from Jambugeulis village. With this fact, the author feels compelled to carry out business management training with marketplace techniques by utilizing the latest developments in information technology. The methods implemented in this community service activity are the Lecture method, the Question and Answer method, and the Simulation method. From the results of the activities that have been carried out, participants are very enthusiastic about participating in the activities and understand the importance of business management by utilizing marketpalce. Key words: Training, business management, marketplace, Jambugeulis village